2017
DOI: 10.3389/fmars.2017.00324
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Niche Shifts of Multiple Marine Predators under Varying Prey Availability on the Northeast Newfoundland Coast

Abstract: Understanding species interactions among top marine predators and interactions with their prey can provide important insight into community-level responses to changing prey availability and the role of apex predators as indicators of ecosystem change. On the northeast Newfoundland coast, marine predators rely on capelin (Mallotus villosus), a dominant forage fish, as a food source. Capelin migrate into coastal regions to spawn during July, essentially transforming the food supply from low during early summer (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 71 publications
5
28
1
Order By: Relevance
“…Previous studies have found a negative relationship between latitude and δ 13 C values in the blood of Cory's shearwaters (Calonectris borealis) in the North Atlantic [48,49]. Therefore, we also compared the δ 13 C and δ 15 N values of great shearwater RBCs and feathers from our study with those from previous studies [34,35,37,46].…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…Previous studies have found a negative relationship between latitude and δ 13 C values in the blood of Cory's shearwaters (Calonectris borealis) in the North Atlantic [48,49]. Therefore, we also compared the δ 13 C and δ 15 N values of great shearwater RBCs and feathers from our study with those from previous studies [34,35,37,46].…”
mentioning
confidence: 86%
“…Three studies that have collected and analyzed data on the δ 13 C and δ 15 N values of RBCs (i.e., the cellular portion of blood) in the North Atlantic ( [34,35] and this study), providing enough data to look for a latitudinal gradient in δ 13 C ( Table 1). We found that δ 13 C decreases significantly with latitude (F 1,10 = 24.07, p = 0.006) and that the relationship explains a high proportion of the variance (R 2 = 0.71; Figure 4A).…”
Section: Latitudinal Gradientmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences arise due to preferential retention of heavier isotopes and excretion of lighter isotopes, leading to relative enrichment in 15 N and 13 C with increasing trophic level (discrimination factors). The amount of 15 N in tissues is indicative of an animal's trophic position, whereas 13 C content can be used to recognize primary sources of carbon (i.e., foraging habitat) (Post, 2002;Gulka et al, 2017). Samples of lobster abdominal (tail) muscle were rinsed with ultrapure MilliQ water, dried completely at 60 • C and ground to a fine powder with agate mortar and pestle; then ∼1 mg of powdered tissue was transferred into tin capsules.…”
Section: Stable Isotope Analysesmentioning
confidence: 99%
“…We did this analysis with Bayesian mixing models (Parnell et al, 2010) using the SIAR package in R (Jackson et al, 2011). Mixing models require the use of discrimination factors, the best of which are those derived from the species under study or, failing that, from closely related species (Gulka et al, 2017). In the absence of specific discrimination factors for P. argus or P. guttatus, we used a range of discrimination factors estimated by Waddington and MacArthur (2008) from tail tissue of spiny lobsters P. cygnus fed various diets (δ 15 N range 1.67-2.97 ; mean 2.57 ; δ 13 C range 2.92-3.60 ; mean 3.20 ).…”
Section: Stable Isotope Analysesmentioning
confidence: 99%